Gomorra - La serie, esempio di transmedialità incompleta - Maria Grazia Falà (Ocula)
Numerous scholars have debated the transmediality of Gomorrah - The Series, offering varying opinions. The thesis we aim to support is that this is a case of incomplete transmediality, primarily due to gaps in Sky Italia's promotional strategies, especially concerning social media. Even a spin-off like L'Immortale (2019) can be considered a makeshift and limited attempt. Simultaneously, it is possible to identify a «Saviano style» to describe the approach of the Campanian author to all his productions, creating a strong bond that connects them all, including his graphic novel Sono ancora vivo. However, in confirmation of the lack of transmediality of Gomorrah - The Series, are the social media activities of its two main protagonists, Salvatore Esposito (Genny Savastano) and Marco D'Amore (Ciro Di Marzio), which focus more on the actor's persona than on their acting performances in the series. Weak transmediality is also confirmed by the activities of the fans that revolve around this product, but are hindered by the production, which, in two Facebook groups, has gone as far as banning clips from Gomorrah - The Series not belonging to official channels.